Infectious thyroiditis as a complication of fine-needle biopsy: a systematic review. Issue 5 (September 2010) - Polyzos, Stergios A; Anastasilakis, Athanasios D
Thyroid fine-needle biopsy (FNB) is a simple, reliable and inexpensive procedure for the diagnosis of thyroid malignancy. Furthermore, it is a useful tool for the identification of the causative pathogen in cases of acute suppurative thyroiditis. However, it can also cause infectious thyroiditis, as bacterial seeding can occur. Post-FNB thyroid infection is a rare complication. Gram-positive bacteria predominate but other bacteria have also been isolated, especially in immunocompromised patients. Preventive measures include iodine skin preparation and alcohol cleansing of the skin before FNB and adequate aseptic conditions. The prognosis of post-FNB infectious thyroiditis depends on prompt recognition and treatment. The treatment of choice is antibiotics and pus drainage, but thyroid resection may be required in cases of persistent infection.